ClpC ATPase Is Required for Cell Adhesion and Invasion of Listeria monocytogenes - Nair, Shamila (American Society for Microbiology, 2000)
We studied the role of two members of the 100-kDa heat shock protein family, the ClpC and ClpE ATPases, in cell adhesion and invasion of the intracellular pathogen Listeria monocytogenes. During the early phase of infection, a clpC mutant failed to disseminate to hepatocytes in the livers of infected mice whereas the invasive capacity of a clpE mutant remained unchanged. This was confirmed by a confocal microscopy study on infected cultured hepatocyte and epithelial cell lines, showing a strong reduction of cell invasion only by the clpC mutant. Western blot analysis with specific antisera showed that the absence of ClpC, but not that of ClpE, reduced expression of the virulence factors InlA, InlB, and ActA. ClpC-dependent modulation of these factors occurs at the transcriptional level with a reduction in the transcription of inlA, inlB, and actA in the clpC mutant, in contrast to the clpE mutant. This work provides the first evidence that, in addition to promoting escape from the phagosomes, ClpC is required for adhesion and invasion and modulates the expression of InlA, InlB, and ActA, further supporting the major role of the Clp chaperones in the virulence of intracellular pathogens.